The Memoirs of Emma Reyes and Flora Tristán: Outcasts or Pioneers? - González Sawczuk, Susana Ynés; Chicangana-Bayona, Yobenj (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper is based on the reflections of the memories of two extraordinary outcasts of our America. On the one hand, Emma Reyes reminds us of the childhood/experience relationship in her letters in Memory by correspondence. They are brief letters that, beyond a certain affective confession, represent stories as a figure of a painful genesis that invite us to immerse ourselves in the procedures of language mediation in suffering, and to realize the experience of grief. While, two centuries before, Flora Tristan, another declassed and fervent social fighter published in France her memories, Peregrinations of a Pariah. Some interpretations are considered in the light of Giorgio Agamben's text, Infancy and History, on the mute experience of childhood, some articles by Mario Vargas Llosa are also discussed.